Glomerular Filtration Rate, its Association with Risk Factors and Cardiovascular Diseases. The Results of the ESSE-RF-2 Study - S. A. Shalnova; S. A. Maksimov; Yu. A. Balanova; S. E. Evstifeeva; A. E. Imaeva; A. V. Kapustina; G. A. Muromtseva; V. I. Tarasov; I. A. Viktorova; A. N. Redko; N. N. Prishchepa; S. S. Yakushin; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To study the influence of social determinants on the frequency of glomerular filtration rate (GFR) categories of various levels, as well as associations with a number of cardiovascular diseases (CVD) and cardiovascular risk factors among the population of four Russian regions included in the ESSE-RF-2.Material and methods. The study was performed as part of a multicenter epidemiological study “Epidemiology of cardiovascular diseases in the regions of the Russian Federation. The second study (ESSE-RF-2)”. In total, 6681 people 25-64 years old from 4 regions of Russian Federation were included in the analysis. The CKD-EPI formula was used to calculate GFR by blood creatinine level. Groups with normal GFR (≥90 ml/min/1.73 m²), with an initial decrease in GFR (<90 ml/min/1.73 m²), and with a decrease in GFR (<60 ml/min/1.73 m²) were distinguished for statistical analysis. Generalized linear/nonlinear analysis (GLM) was used for multivariate assessment and adjustment of results to socio-demographic characteristics.Results. The average GFR level in the total sample was 97.8±16.6 ml/min/1.73 m2 ; 29.0% of individuals had an initial decrease in GFR, 1.6% had a reduced GFR. Age was significantly associated with GFR. A statistically significant association with an initial decrease in GFR was found for: hypercholesterolemia (odds ratio [OR] 1.22; 95% clearance interval [95%CI] 1.14-1.30), hypertriglyceridemia (OR 1.09; 95%CI 1.02-1.17), hyperuricemia (OR 1.51; 95%CI 1.39-1.63), no smoking (OR 0.79; 95%CI 0.73-0.85), history of kidney disease (OR 1.13; 95%CI 1.04-1.22). A more pronounced decrease in GFR was associated with the following factors and diseases: arterial hypertension (OR 1.48; 95%CI 1.07-2.05), low level of high-density lipoproteins (OR 1.36; 95%CI 1.04-1.79), hypertriglyceridemia (OR 1.37; 95%CI 1.08-1.76), hyperuricemia (OR 2.49; 95%CI 1.97-3.16), hyperglycemia (OR 1.35; 95%CI 1.01-1.80), a history of myocardial infarction (OR 1.63; 95%CI 1.13-2.36) and kidney disease (OR 1.50; 95%CI 1.16-1.93).Conclusion. The results of the study indicate a greater number of factors and diseases associated with low GFR compared with the initial decrease, which emphasizes the need for early detection of signs of chronic kidney disease, especially in the elderly, in people with metabolic syndrome, hypertension or diabetes mellitus, as well as a history of kidney disease.